Utivarachna rama sp. n., a new species of tracheline spiders (Araneae: Corinnidae) from Thailand - Thanaphum Chami-Kranon (2018)
A new species of tracheline spiders, Utivarachna ratna Chami-Kranon & Likhitrakarn sp. n., is described. The types were collected from pristine forests of the Doi Inthanon National Park, Chiang Mai Province, northern Thailand. The new species belongs to the kinabaluensis-group and can be distinguished from its congeners by the gradually tapering retrolateral tibial apophysis of the male palp, and by the posteriorly rounded epigynal atrium, the reniform spermathecae, and the anterior bursae with long, narrow necks in females. Utivarachna rama sp. n. is closely related to U. bucculenta Deeleman-Reinhold, 2001 and U. kinabaluensis Deeleman-Reinhold, 2001. Copyright © 2007 Magnolia Press.